Peran Komunitas Gerakan Anti Kekerasan (GAK) dalam Advokasi Kekerasan Berbasis Online (KBGO) - Fitria Juliana; Yustika Irfani Lindawati (Universitas Hamzanwadi, 2026)
This study examines the role of the Generasi Anti Kekerasan (GAK) community in responding to Online Gender-Based Violence (OGBV) in Indonesia, particularly cyberbullying, doxing, online harassment, and digital discrimination. The study aims to analyze how GAK carries out digital education, victim advocacy, anti-victim blaming campaigns, and cross-sector collaboration in addressing technology-facilitated gender-based violence. This research employed a qualitative approach using a descriptive case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving members and facilitators of the GAK community.The findings reveal that GAK functions as a digital social movement that not only disseminates information regarding OGBV prevention, but also builds collective awareness, solidarity, and victim-centered advocacy practices. GAK conducts digital literacy education through social media campaigns, public discussions, hashtag activism, and capacity-building activities aimed at increasing awareness of digital safety and gender justice. The study also shows that victim assistance requires emotional support, digital protection, legal referral mechanisms, and collaborative networks involving educational institutions, psychologists, civil society organizations, and digital platforms.This study highlights that grassroots digital communities play a strategic role in creating safer digital spaces and strengthening gender-sensitive digital citizenship. The findings contribute to the development of studies on digital sociology, feminist digital activism, and community-based advocacy in addressing Online Gender-Based Violence in Indonesia.